The automatization of press statistics as one of the ways to improve the service of information users - Šarlauskienė, Angelė (Knygotyra, 1990)
The Department of Press Statistics at the Book Palace of Lithuania is the first in the Soviet Union to apply computers for preparing quick accounts of gathered information. This significantly helps to regulate book production and its thematic planning. The Department of Press Statistics functions independently as a constituent part of the automatization of press statistics in the Book Palace. The rapid and precise handling of statistical tasks, which reflects the basic tendencies of press production activities, enables the improvement of the press production process. The grouping and gathering of the main features of the press and the analysis of statistical feedback help to use computers in the most rational way to increase the capacity for solving statistical tasks.